Vytápění objektu - Král, Daniel (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Tato bakalářská práce se zabývá návrhem systému ústředního vytápění pro přístavbu a rekon-strukci obecního úřadu s víceúčelovým sálem. Cílem práce je navrhnout technicky proveditelné, energeticky úsporné a ekonomicky efektivní řešení, které bude v souladu s platnou legislativou a příslušnými normami. Teoretická část se podrobně věnuje principům sálavého přenosu tepla, výhodám a nevýhodám sálavých stropních panelů a jejich porovnání s jinými otopnými systémy. Dále se zaměřuje na provozně-technické a konstrukčně-technické hledisko těchto zařízení. Prak-tická část obsahuje analýzu objektu, výpočet tepelných ztrát, návrh zdroje tepla a dimenzování otopné soustavy s využitím sálavých panelů.

This bachelor thesis deals with the design of a central heating system for the extension and re-construction of a municipal office building with a multifunctional hall. The aim of the work is to propose a technically feasible, energy-efficient and economically effective solution that com-plies with current legislation and applicable technical standards. The theoretical part focuses on the principles of radiant heat transfer, the advantages and disadvantages of ceiling radiant pa-nels, and their comparison with other heating systems. Furthermore, it examines the operatio-nal and constructional aspects of these devices. The practical part includes a building analysis, heat loss calculation, heat source selection, and the design and dimensioning of the heating sys-tem using radiant panels.
Heating of Building
Keywords: sálavé stropní panely; otopné soustavy; tepelný výkon; hydraulické vyvážení; kondenzační kotle; normy ČSN; legislativa EU; tepelný odpor; součinitel prostupu tepla; radiant ceiling panels; heating systems; thermal output; hydraulic balancing; condensing boilers; ČSN standards; EU legislation; thermal resistance; heat transfer coefficient